Nebuchadnezzar’s Siege of Tyre in Jerome’s "Commentary on Ezekiel" - Garstad, Benjamin (2016)
In order to elucidate the prophecies of Ezekiel, especially those against Egypt in Book 29, Jerome reconstructed the siege of Tyre by the Babylonian king Nebuchadnezzar. He seems to have done this not so much on the basis of the predictions recorded in the Bible (to say nothing of accurate records), as by comparison with accounts of Alexander the Great’s siege of the same city more than two hundred years later. Jerome seems particularly dependent on the account of Alexander’s siege of Tyre given by Quintus Curtius Rufus. The following investigation broadens our understanding of the authors known and used by Jerome, the uses to which he put his historical reading, and the methods of his Biblical exegesis, especially historical reconstruction.
Keywords: Jerome -- Ezekiel -- Tyre -- Nebuchadnezzar -- Alexander -- Quintus Curtius Rufus -- Biblical Commentaries